Seaweed tea: fucoidan-rich functional food product development from Malaysian brown seaweed, Sargassum binderi - Lim, Seng Joe; Wan Aida Wan Mustapha,; Mohamad Yusof Maskat, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Our previous studies on fucoidan from Malaysian brown seaweed, Sargassum binderi, found that it exhibited significant secondary anti-oxidative activity and showed non-toxicity. In order to exploit its health benefits, fucoidan-rich seaweed tea was developed in this study. A total of 4 different brewing time treatments were performed on Sargassum binderi at 5, 10, 15 and 20 mins (Ft05, Ft10, Ft15 and Ft20, respectively). It was found that Ft20 showed significantly (p<0.05) highest fucoidan content (27.22 ± 0.07 mg/200 mL), superoxide anion scavenging activity (16.46 ± 2.83%) and hydroxyl radical scavenging activity (89.83 ± 4.11%) compared to that of Ft05, Ft10 and Ft15. Both the secondary antioxidant activities were significantly positive correlated to the fucoidan content tests (superoxide anion scavenging activity at r=0.97, p=0.0052; and hydroxyl radical scavenging activity at r=0.99, p=0.0011). Masking of the seaweed odour was performed using lemon essence and discriminative test found that masking was most effective using lemon essence at a concentration of 0.3% (v/v). Therefore, there is potential for this seaweed tea to be commercialised, thus, consumers may acquire the health benefit of fucoidan.